4-(3-Fluorophenyl)-1-(propan-2-ylidene)thiosemicarbazone - Barbara Miroslaw; Daniel Szulczyk; Anna E. Koziol; Marta Struga (Acta Crystallographica Section E, 2011)
The title compound, C10H12FN3S, crystallizes in the same space group (P21/c) as two polymorphic forms of 4-phenyl-1-(propan-2-ylidene)thiosemicarbazone [Jian et al. (2005). Acta Cryst. E61, o653–o654; Venkatraman et al. (2005). Acta Cryst. E61, o3914–o3916]. The arrangement of molecules relative to the twofold screw axes is similar to that in the crystal structure of the lower density polymorph. In the solid state, the molecular conformation is stabilized by an intramolecular N—H...N hydrogen bond. The molecules form centrosymmetric R22(8) dimers in the crystal through pairs of N—H...S hydrogen bonds.